2011
DOI: 10.1249/mss.0b013e318204de1c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Association between HR Variability and Illness in Elite Swimmers

Abstract: Swimmers' health maintenance requires particular attention when autonomic balance shows a sudden increase in parasympathetic indices in the supine position assessed 1 wk earlier evolving toward sympathetic predominance in supine and orthostatic positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Limiting pathogen exposure in the aquatic environment is important given evidence of water quality issues in swimming pools (McCann et al, 2013;Sanborn & Takaro, 2013) and freshwater and marine (Arnold et al, 2013) environments. Other factors influencing the risk of illness include season, with a higher risk of URTIs in winter months (Hellard et al, 2011).…”
Section: Nutritional Recommendations For Injury and Illness Preventiomentioning
confidence: 99%
“…Limiting pathogen exposure in the aquatic environment is important given evidence of water quality issues in swimming pools (McCann et al, 2013;Sanborn & Takaro, 2013) and freshwater and marine (Arnold et al, 2013) environments. Other factors influencing the risk of illness include season, with a higher risk of URTIs in winter months (Hellard et al, 2011).…”
Section: Nutritional Recommendations For Injury and Illness Preventiomentioning
confidence: 99%
“…(2) illness (Hellard et al 2010); (3) overtraining (Pelayo et al 1996) or; (4) preference to improve academic success instead of sports performance.…”
Section: Normative Stabilitymentioning
confidence: 99%
“…Some accessible data also indicate the connection between autonomic regulation and infections. Hellard et al (2011) analyzed autonomic regulation in swimmers and found that the weeks which preceded occurrence of not only upper respiratory tract and pulmonary infections but also muscular affections were characterized by an increase in autonomic parasympathetic activity in supine position [66]. In fact, the increase in the parasympathetic nervous system is regarded as beneficial for cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%